Diskursive Verfestigungen Schnittstellen zwischen Morphosyntax, Phraseologie und Pragmatik im Deutschen und im Sprachvergleich - Gautier, Laurent; Modicom, Pierre-Yves; Vinckel-Roisin, Hélène (Konvergenz und Divergenz, 2018)
The concept of frozenness has helped to shape recent lexicographic and phraseological research. The essays in this volume form a part of this current trend and examine discursive aspects of the problematics of frozenness and stability, including grammaticalization, lexicalization, and phraseology. Each essay explores phenomena of frozenness in discourse at the interface between pragmatics and morphology/syntax.